The future of neurological patient registries. (September 2014) - Korngut, Lawrence; Johnston, Megan; Pringsheim, Tamara; Jetté, Nathalie
Patient registries represent an important platform across geographical areas that can provide critical epidemiological data and information on the effectiveness of therapies or devices within a given disease group. Neurological patient registries represent an exciting opportunity to directly impact patient care and clinical trial readiness. Neurological registries also aid in the formulation of investigator networks and support translational research pipelines enhancing collaboration and cost–effectiveness of clinical research. Registries collecting high-quality data with near complete to complete ascertainment have the ability to generate useful knowledge about diseases, which is more generalizable to larger disease populations.